ШЛЯХИ ПІДВИЩЕННЯ ЕКОНОМІЧНОСТІ СПОЖИВАННЯ ЕЛЕКТРИЧНОЇ ЕНЕРГІЇ В ЖИТЛОВОМУ СЕКТОРІ - Мартинюк , О.В. (Інститут електродинаміки НАН України, Київ, 2016)
This paper deals with the analysis and modeling of energy consumption in the residential sector An analysis of tariff policy in Ukraine is numerically shown the advantages of using two-zone metering system at the example of a private apartment. A mathematical model of energy consumption with the influence of the apartment calendar, meteorological and astronomical factors. Using the model enables the prediction of electricity consumption in the apartment and to quantify the effectiveness of energy conservation measures.  References 6, tables 3, figures 4.